From Energy-intensive to Innovation-led Growth: On the Transition Dynamics of Chinas Economy - Wei Jin; ZhongXiang Zhang (Fondazione Eni Enrico Mattei (FEEM), 2014)
Whether China continues its current energy-intensive growth path or adopts a sustainable development prospect has significant implication for energy and climate governance. Building on a Ramsey-Cass-Koopmans growth model incorporating the mechanism of endogenous technological change and its interaction with fossil energy use and economic growth, this paper contributes to an economic exposition of Chinas potential transition from an energy-intensive to an innovation-led growth path. We find that in Chinas initial growth period the small amount of capital stock creates higher dynamic benefits of capital investment and incentives of capital stock accumulation rather than R&D-related innovation. Accumulation of energy-consuming capital stock along this non-innovation-led growth path thus leads to an intensive use of fossil energy - an energy-intensive growth pattern. To avoid this undesirable outcome, Chinas social planner should consider locating a transition point to an innovation-led balanced growth path (BGP). When the growth dynamics reaches that transition point, Chinas economy would embark on investment in physical capital and R&D simultaneously, and make a transition into the innovation-led BGP along which consumption, capital investment, and R&D have a balanced share. Also in this innovation-led BGP, consumption, physical capital stock, and knowledge stock all grow, fossil energy uses decline.
Keywords: Q55; Q58; Q43; Q48; O13; O31; O33; O44; F18; 330; Technological Innovation; Energy Consumption; Economic Growth Model